THE EFFECT OF CASH TURNOVER AND RECEIVABLES TURNOVER ON PROFITABILITY IN TOURISM UBSECTOR SERVICES COMPANIES AND HOTEL PERIOD 2010-2019 - Sarining Pujiati, Retno Dwi; Suparno, Suparno (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
This reseacrh aimed to determine the effect of cash turnover and receivable turnover on profitability which is proxied partially or simultaneously on Return On Assets (ROA). The method in this study uses a quantitative approach. The population in this study is the tourism and hotel subsector service companies listed on the Indonesia Stock Exchange in the period 2010-2019. The research sample was taken using a purposive sampling method with units of analysis of 4 companies, data analysis using the classic assumption test, multiple linear regression and statistical tests (t test and f test). Based on data processing the results of this study indicate that partially cash turnover has no significant and significant effect on profitability and accounts receivable turnover has a negative effect but significant on profitability. Simultaneously cash turnover and accounts receivable turnover have a positive and significant effect on profitability.